Quality assurance guidance for scoring and reporting for pathologists and laboratories undertaking clinical trial work - Robinson, M; James, J; Thomas, G; West, N; Jones, L; Lee, J; Oien, K; Freeman, A; Craig, C; Sloan, P; Elliot, P; Cheang, M; et al. (Wiley, 2018)
While pathologists have always played a pivotal role in clinical trials ensuring accurate diagnosis and staging, pathology data from prognostic and predictive tests are increasingly being used to enrol, stratify and randomise patients to experimental treatments. The use of pathological parameters as primary and secondary outcome measures, either as standalone classifiers or in combination with clinical data, is also becoming more common. Moreover, reporting of estimates of residual disease, termed ‘pathological complete response’, have been incorporated into neoadjuvant clinical trials. Pathologists have the expertise to deliver this essential information and they also understand the requirements and limitations of laboratory testing. Quality assurance of pathology‐derived data builds confidence around trial‐specific findings and is necessarily focused on the reproducibility of pathological data, including ‘estimates of uncertainty of measurement’, emphasising the importance of pathologist education, training, calibration and demonstration of satisfactory inter‐observer agreement. There are also opportunities to validate objective image analysis tools alongside conventional histological assessments. The ever‐expanding portfolio of clinical trials will demand more pathologist engagement to deliver the reliable evidence‐base required for new treatments. We provide guidance for quality assurance of pathology scoring and reporting in clinical trials.